Smoking, Hijab and Gender Identity: Social Jurisprudence Perspective on Indonesian Muslim Women in Café Bars - Mafrukha, Wahyu Nisawati; J. Thalgi, Mohammad; Harahap, Sarah Khairani; Nasrullah, Ar Rasyid Fajar; Hamida Nurul Azizah (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2025)
Indonesian Ulema Council (MUI) in 2009 declared that smoking is ḥarām for women, and children, or when held in public places. However, these practices still happen now. It triggers researchers to explore; how the wider social environment regulates the process of internalization and normalization of smoking among Muslim women and the uninvited norms that are religious and social; how religion, gender, and socio-cultural relations shape the attitudes and behavior of Muslim women smoking, and; how social jurisprudence views those problems. This study uses a qualitative approach, which includes observation, interviews, and a literature review with descriptive analysis that considers the principles of social jurisprudence in socio-religious relations. Conducted with an interpretive qualitative paradigm and from a phenomenological epistemology, the study employs the habitus theory by Pierre Bourdieu as well as agency, piety, and embodiment by Eva F. Nisa to explore the intersectionality of faith, culture, and individual agency. Five Muslim women interviewed from five different provinces of Indonesia show how religious ideals clash with gender norms and modernity. The study indicates that familial factors, peers, and media socialization overshadow religious prohibitions against smoking. People adjust religious teachings to specific situations in the way they want since they do not wish the fatwa to control their lives. The café bar is a counter space where women perform defiance and assert ethnic otherness while adhering to patriarchal and religious expectations. Tobacco advertising, in particular, relates views of smoking to economic factors that also contribute to the associated stereotypes of modernity and freedom.